2018
DOI: 10.1186/s13063-018-2526-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of community-level interventions to increase early initiation of antenatal care in pregnancy: protocol for the Community REACH study, a cluster randomised controlled trial with integrated process and economic evaluations

Abstract: BackgroundThe provision of high-quality maternity services is a priority for reducing inequalities in health outcomes for mothers and infants. Best practice includes women having their initial antenatal appointment within the first trimester of pregnancy in order to provide screening and support for healthy lifestyles, well-being and self-care in pregnancy. Previous research has identified inequalities in access to antenatal care, yet there is little evidence on interventions to improve early initiation of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…For example, Satwell et al have designed an intervention to overcome some of the barriers identified in this study, including lack of health literacy, by co‐producing an intervention with the involvement of their community to reduce the high rates of late initiation of antenatal care in the UK. The intervention is co‐produced and locally tailored to each participating site (Sawtell et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Satwell et al have designed an intervention to overcome some of the barriers identified in this study, including lack of health literacy, by co‐producing an intervention with the involvement of their community to reduce the high rates of late initiation of antenatal care in the UK. The intervention is co‐produced and locally tailored to each participating site (Sawtell et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there are many examples of national epidemiological research and audit conducted using EPR data over the past 20 years [ 2 ], clinical trials using data collected from EPR have only become more prevalent in the last 5 years. Examples in maternal and perinatal medicine come from Canada [ 3 ], Sweden [ 4 ], the Netherlands [ 5 ], Scotland [ 6 , 7 ], Wales [ 8 ] and England [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While academic-practitioner collaboration in the conduct of RCTs is increasingly common, it remains relatively unusual for allied health professionals, including midwives, to be at the centre of such research. In this study, as with others in the REACH programme [44], the aim will be to have midwives as key collaborators at both central research and site team level (for example as site Principal Investigators). This will not only help to maximise the rigour, relevance and success of the work but also build research capacity in the midwifery profession and NHS trust maternity research teams.…”
Section: Discussionmentioning
confidence: 99%